2008
DOI: 10.1016/j.eplepsyres.2008.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Long-term decrease in calbindin-D28K expression in the hippocampus of epileptic rats following pilocarpine-induced status epilepticus

Abstract: SummaryAcquired epilepsy (AE) is characterized by spontaneous recurrent seizures and long-term changes that occur in surviving neurons following an injury such as status epilepticus (SE). Long-lasting alterations in hippocampal Ca 2+ homeostasis have been observed in both in vivo and in vitro models of AE. One major regulator of Ca 2+ homeostasis is the neuronal calcium binding protein, calbindinD28k that serves to buffer and transport Ca 2+ ions. This study evaluated the expression of hippocampal calbindin le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 49 publications
1
25
0
1
Order By: Relevance
“…Recently, we have shown that the degree of loss of CB in the granule cells is correlated with the age of onset and the duration of TLE [19]. This observation along with that of animal models of epilepsy suggest that decrease of CB mRNA and protein expression in the granule cells is a consequence of neuronal hyperactivity [66]. In fact, in animal models of TLE, the decreased CB expression can be detected only ipsilaterally but not contralaterally [67].…”
Section: Discussionmentioning
confidence: 93%
“…Recently, we have shown that the degree of loss of CB in the granule cells is correlated with the age of onset and the duration of TLE [19]. This observation along with that of animal models of epilepsy suggest that decrease of CB mRNA and protein expression in the granule cells is a consequence of neuronal hyperactivity [66]. In fact, in animal models of TLE, the decreased CB expression can be detected only ipsilaterally but not contralaterally [67].…”
Section: Discussionmentioning
confidence: 93%
“…, protect the normal activation and function of the neuron and inhibit the apoptosis of neuron induced by the overload of intracellular Ca 2? (Meng et al 2007;Carter et al 2008). Pretreatment with paeoniflorin dose-dependently decreased intracellular Ca 2?…”
Section: Discussionmentioning
confidence: 98%
“…Esto coincide con nuestros estudios previos en los que se demostró pérdida de CB en la corteza cerebral, el cuerpo estriado y el hipocampo (13,14,18). En diferentes afecciones del sistema nervioso central se ha encontrado disminución de la expresión de CB, por ejemplo, reducción del número de células de Purkinje positivas para CB en casos de degeneración espinocerebelar (27), así como disminución de la expresión de esta proteína en el hipocampo de ratas epilépticas (28). Son escasas las referencias relacionadas con pérdida de CB en la médula espinal.…”
Section: Efecto De La Infección Viral Sobre La Expresión De Cb Y Pvunclassified